The languages of Africa and the diaspora [ educating for language awareness - Bond, George C.; Kleifgen, Jo Anne (New perspectives on language and education, 2009)
Takes a fresh look at subordinated vernacular languages in the context of African, Caribbean, and US educational landscapes, highlighting the social cost of linguistic exceptionalism for speakers of these languages. This title also offersa comprehensive approach to language awareness in educative settings.